Impact of a ‘Research in pharmacy’ course on students’ self-reported competence and confidence to conduct research: findings from a Malaysian university - Abubakr, Usman; Elnaem, Mohamed Hassan Abdelaziz; Ahmed, Abdulkareem Mohammed; Zaini, Syahrir; Nahas, Abdul Rahman Fata; Shamsudin, Siti Hadijah (FIP International Pharmaceutical Federation, 2022)
Objective: To evaluate the impact of a ‘Research in Pharmacy’ course on students’ self-reported competence and confidence to plan and conduct pharmacy practice research. Method: This is a pre- and post-intervention study conducted among third year pharmacy undergraduate students in a public university in Malaysia using an online questionnaire. A ‘Research in pharmacy’ course which encompassed lectures, tutorials, and practical sessions was delivered over a 14-week period. The students were divided into groups and assigned a project supervisor to guide them in planning and conducting a research project that was completed in one term. Result: Of the 109 students, 69 and 62 completed the questionnaire in the pre- and postintervention periods, respectively. Students’ interest in conducting research and their interest in learning about research was similar in both periods. However, self-reported ability to conduct research increased significantly. Self-reported competence and confidence to conduct most components of research improved significantly (p < 0.05), although, extreme/very competent or confidence level was lower than 50% for most items. Overall, median total competence score (66.0 versus 74.0, p < 0.001) and median total confidence score (66.0 versus 71.5, p < 0.001) increased significantly after the course. Most students were very satisfied/satisfied with the online lectures (54.8%) and online project supervision (64.6%). Lack of time (61.3%) was the major challenge students encountered during the course. Conclusion: A ‘Research in pharmacy' course with both didactic and experiential components improved self-reported competence and confidence to plan and conduct research among pharmacy undergraduate students. Future studies should investigate the facilitators and barriers to students’ interest in pharmacy practice research.